Modeling Seasonal Variability of Trophic Index (TRIX) in Indonesian Waters Using PISCES Biogeochemical Data - Krisna, Heru Nur; Maslukah, Lilik; Wirasatriya, Anindya; Indrayanti, Elis; Widiaratih, Rikha (Marine Science Department Diponegoro University, 2025)
Eutrophication poses a significant challenge in Indonesian waters, largely due to a lack of data for effective mitigation. This complex issue, characterized by a time lag and multi-phase progression, is triggered by an influx of nutrients like nitrate and phosphate, leading to harmful algal blooms (HABs) that degrade water quality. This study proposes a more comprehensive approach using the Trophic Index (TRIX), which integrates multiple parameters from the PISCES global biogeochemical model data. The PISCES model accurately captures seasonal TRIX trends, with high values in the southern islands during the southeast monsoon and in northern areas during the northwest monsoon. The model's reliability is confirmed by RMSE and Bias data to be quite low, respectively, for Chl-a (0.065, -0.005), Nitrate (0.144, -0.080), Phosphate (0.084, -0.059), and DO (3.109, 0.919), from the World Ocean Database. The highest TRIX values (8-10) were found in Jakarta Bay, while the Lombok Strait had values (5-7), a difference attributed to varying oceanographic conditions. However, it is crucial to consider physical oceanography and boundary conditions when using the TRIX model. So then, model TRIX data is more valuable for informing policy and mitigation plans for the various Indonesian waters, taking into account their unique characteristics. These findings underscore the importance of considering both monsoon cycles and local conditions when assessing eutrophication risk. The TRIX data is therefore a valuable tool for developing informed policies and mitigation plans for Indonesia's diverse coastal areas.